El crecimiento económico en el Perú - Loayza, Norman V. (2008)
This paper analyzes the experience of economic growth in Peru during the last five decades. It describes its principal characteristics, explains the changes along the period and predicts its future path. The methodological approach consists in a combination of accounting and econometric techniques, both based in comparisons between countries and periods of time. The study discovers that the most important turning points of the economic growth were caused by changes in the productivity of all inputs, instead of the simple accumulation of capital. Specifically, the paper finds out that the recover of the economic growth in Peru during the 1990’s was caused by the process of structural reforms and stabilization and lasts until now. The future growth of the economy depends on the continuation and deepness of this process.